Sistema para a Predição do Crescimento da Cortiça - Almeida, Alice; Tomé, Margarida (Silva Lusitana, 2008)
. Cork growth modelling was based on two models: cork growth model for complete rings and a model for total cork thickness prediction. The cork growth model was developed using data from 189 cork samples taken at breast height. Four biological growth functions were considered using their formulation as difference equations. The evaluation of the fitting and predictive ability of the models was based on model efficiency and on several statistics computed with the press residuals, complemented with graphical analysis to assess the regression assumptions. The model selected - Lundqvist-A - can be used to predict cork thickness in complete rings at any year of the cork rotation. The model for the prediction of total cork thickness is used to predict total cork thickness from the thickness in complete rings
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: accumulated cork thickness in complete rings; cork growth; growth models; prediction; total cork thickness prediction

Sistema para a Predição do Crescimento da Cortiça - Almeida, Alice; Tomé, Margarida (Silva Lusitana, 2008)
. Cork growth modelling was based on two models: cork growth model for complete rings and a model for total cork thickness prediction. The cork growth model was developed using data from 189 cork samples taken at breast height. Four biological growth functions were considered using their formulation as difference equations. The evaluation of the fitting and predictive ability of the models was based on model efficiency and on several statistics computed with the press residuals, complemented with graphical analysis to assess the regression assumptions. The model selected - Lundqvist-A - can be used to predict cork thickness in complete rings at any year of the cork rotation. The model for the prediction of total cork thickness is used to predict total cork thickness from the thickness in complete rings
Keywords: accumulated cork thickness in complete rings; cork growth; growth models; prediction; total cork thickness prediction

Influence of climate on the seasonality of radial growth of cork oak during a cork production cycle - Costa, Augusta; Pereira, Helena; Oliveira, Ângelo (Ann. For. Sci., 2002)
The radial growth of mature cork oaks (Quercus suber L.) was studied during a 9-year production cycle using monthly dendrometer measurements and cork ring widths. The mean tree radial increase was 5.1 mm yr -1 and the cork increment accounting for 3.8 mm yr -1. The radial growth curves for cork, wood and stem were very similar, showing a decreasing trend along the production cycle. Cork increment was always the largest fraction of tree growth (on average 74%) and showed less inter-annual variations as compared to wood. Tree radial growth presented a clear within-the-year seasonal pattern, extending from March to October, with a maximum in June-July. The overall pattern of monthly growth distribution was similar among the years of the production cycle, but some inter-annual variations occurred with 1-2 month shifts or monthly growth rate decreases, related to climatic factors. Early spring growth was enhanced by winter rain, autumn growth by high summer rain and June increments by high temperatures during this month.
Keywords: climatic fluctuations; cork growth; Cork oak; dendroclimatology; diameter growth

Influence of climate on the seasonality of radial growth of cork oak during a cork production cycle - Costa, Augusta; Pereira, Helena; Oliveira, Ângelo (Ann. For. Sci., 2002)
The radial growth of mature cork oaks (Quercus suber L.) was studied during a 9-year production cycle using monthly dendrometer measurements and cork ring widths. The mean tree radial increase was 5.1 mm yr -1 and the cork increment accounting for 3.8 mm yr -1. The radial growth curves for cork, wood and stem were very similar, showing a decreasing trend along the production cycle. Cork increment was always the largest fraction of tree growth (on average 74%) and showed less inter-annual variations as compared to wood. Tree radial growth presented a clear within-the-year seasonal pattern, extending from March to October, with a maximum in June-July. The overall pattern of monthly growth distribution was similar among the years of the production cycle, but some inter-annual variations occurred with 1-2 month shifts or monthly growth rate decreases, related to climatic factors. Early spring growth was enhanced by winter rain, autumn growth by high summer rain and June increments by high temperatures during this month.
Keywords: climatic fluctuations; cork growth; Cork oak; dendroclimatology; diameter growth

The influence of cork oak pruning on the yield and growth of cork - Cañellas, Isabel; Montero, Gregorio (Ann. For. Sci., 2002)
Bearing in mind the importance of pruning as a silvicultural treatment in cork oak (Quercus suber L.) open woodland of the dehesa type, an experiment was designed to assess the effect of pruning on cork yield. This work was carried out in two ways: synchronically, comparing pruned sites with others which were either unpruned or pruned at different times, and diachronically, comparing pruned and unpruned trees within the same site. The five test sites (with forty trees in the synchronic and eighty in the diachronic plots) were selected in south-west Spain. In all cases measurements of the cork production were made in kilos per square metre of surface stripped, total cork yield per tree, and the mean thickness of stripped cork. Analysis was carried out using a paired data comparison test. The effect of pruning on yearly cork growth was also analysed by examining the annual growth rings. In the five plots analysed there were no significant differences (95% confidence intervals) between pruned and unpruned trees in terms of kilos of cork produced per square metre of surface stripped, nor for total cork yield per tree. Neither were there significant differences in annual cork growth rings, even when the pruning was carried out during the cork-stripping period.
Keywords: cork growth; Cork Production; pruned biomass; pruning; Quercus suber

Influence of weather on cork-ring width - Caritat, Antònia; Gutiérrez, Emilia; Molinas, Marisa (Tree Physiology, 2000)
Ring-width series of cork from Quercus suber L. trees growing at two sites in Extremadura (southwestern Spain) were analyzed in relation to monthly precipitation and temperature, and to climatic indices combining both variables. Ring width of cork showed strong positive correlations with precipitation, especially during the fall and winter. Moderately low temperatures were favorable for cork growth, except in winter and during the onset of phellogen activity. We conclude that drought or temperature, or both, can limit cork growth during the annual drought period.
10.1093/treephys/20.13.89310.1093/treephys/20.13.893
Keywords: climatic variability; cork growth; cork-ring chro- nology; dendroclimatology; phellogen activity; Quercus suber

Influence of weather on cork-ring width - Caritat, Antònia; Gutiérrez, Emilia; Molinas, Marisa (Tree Physiology, 2000)
Ring-width series of cork from Quercus suber L. trees growing at two sites in Extremadura (southwestern Spain) were analyzed in relation to monthly precipitation and temperature, and to climatic indices combining both variables. Ring width of cork showed strong positive correlations with precipitation, especially during the fall and winter. Moderately low temperatures were favorable for cork growth, except in winter and during the onset of phellogen activity. We conclude that drought or temperature, or both, can limit cork growth during the annual drought period.
10.1093/treephys/20.13.893
Keywords: climatic variability; cork growth; cork-ring chro- nology; dendroclimatology; phellogen activity; Quercus suber

Annual cork-ring width variability of Quercus suber L. in relation to temperature and precipitation (Extremadura, southwestern Spain) - Caritat, A; Molinas, M; Gutiérrez, E (Forest Ecology and Management, 1996)
A 14 year sequence of cork-ring width chronology is correlated with rainfall and temperature data. Cork specimens were obtained from three cork peel samplings carried out in 1989, 1991 and 1993 from a cork ‘dehesa’ in Ckeres, Spain. Average width of cork-rings varied between 2.05 and 4.37 mm. The cork-ring width chronologies of the three peel-off samplings show definite agreement patterns. Differences in ring width in years of greater and lesser growth are clearly marked. Correlation between ring width and rainfall indicates that the rain periods with the greatest influence on cork growth are those occurring from November to June, followed by those from November to September. Temperature, on the other hand, shows a negative correlation with cork growth, except during the coldest months and the months of April and September when temperature possibly has a crucial influence on phellogen activation.
Keywords: climatic fluctuations; cork growth; cork-oak; cork-ring chronology; Quercus suber L.

Annual cork-ring width variability of Quercus suber L. in relation to temperature and precipitation (Extremadura, southwestern Spain) - Caritat, A.; Molinas, M.; GUTIÉRREZ, E. (Forest Ecology and Management, 1996)
A 14 year sequence of cork-ring width chronology is correlated with rainfall and temperature data. Cork specimens were obtained from three cork peel samplings carried out in 1989, 1991 and 1993 from a cork ‘dehesa’ in Ckeres, Spain. Average width of cork-rings varied between 2.05 and 4.37 mm. The cork-ring width chronologies of the three peel-off samplings show definite agreement patterns. Differences in ring width in years of greater and lesser growth are clearly marked. Correlation between ring width and rainfall indicates that the rain periods with the greatest influence on cork growth are those occurring from November to June, followed by those from November to September. Temperature, on the other hand, shows a negative correlation with cork growth, except during the coldest months and the months of April and September when temperature possibly has a crucial influence on phellogen activation.
Keywords: climatic fluctuations; cork growth; cork-oak; cork-ring chronology; Quercus suber L.